Effect of Immersive Virtual Reality Teamwork Training on Safety Behaviors During Surgical Cases: Nonrandomized Intervention Versus Controlled Pilot Study - Lukasz Mazur; Logan Butler; Cody Mitchell; Shaian Lashani; Shawna Buchanan; Christi Fenison; Karthik Adapa; Xianming Tan; Selina An; Jin Ra (JMIR Medical Education)
Abstract BackgroundApproximately 4000 preventable surgical errors occur per year in the US operating rooms, many due to suboptimal teamwork and safety behaviors. Such errors can result in temporary or permanent harm to patients, including physical injury, emotional distress, or even death, and can also adversely affect care providers, often referred to as the “second victim.” ObjectiveGiven the persistence of adverse events in the operating rooms, the objective of this study was to quantify the effect of an innovative and immersive virtual reality (VR)–based educational intervention on (1) safety behaviors of surgeons in the operating rooms and (2) sense-making regarding the overall training experience. MethodsThis mixed methods pre- versus postintervention pilot study was conducted in a large academic medical center with 55 operating rooms. Safety behaviors were observed and quantified using validated Teamwork Evaluation of Non-Technical Skills instrument during surgical cases at baseline (101 observations; 83 surgeons) and postimmersive VR based intervention (postintervention: 24 observations within each group; intervention group [with VR training; 10 surgeons] and control [no VR training; 10 surgeons]). VR intervention included a 45-minute immersive VR-based training incorporating a pre- and postdebriefing based on Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS) principles to improve safety behaviors. A 2-tailed, 2-sample t ResultsPreintervention, all safety behaviors averaged slightly above “acceptable” scores, with an overall average of 2.2 (range 2‐2.3; 0‐3 scale). The 10 surgeons that underwent our intervention showed statistically significant (P ConclusionsVR-based immersive training intervention focused on TeamSTEPPS principles seems effective in improving safety behaviors in the operating rooms as quantified via observations using the Teamwork Evaluation of Non-Technical Skills instrument. Further research with larger, more diverse sample sizes is needed to confirm the generalizability of these findings.